Ð¡assette Vibration Installation Mathematical Modeling for Compacting Concrete Mix During the Formation Reinforced Concrete Products - Nesterenko Sr., Mykola; Maslov, Alexander; Molchanov, Petro; Salenko, Yulia (International Journal of Engineering and Technology, 2018)
Calculated scheme of the vibration unit with the spatial motion of the working body is proposed and a mathematical model of the vibration plant is created taking into account the resistance of the compacted mixture to the working body, which allows more precisely to design vibration machines for the production of reinforced concrete and concrete products, which is an extremely urgent task, especially in modern market conditions.Â Â